Permanent neonatal diabetes caused by creation of an ectopic splice site within the INS gene. - Intza Garin; Guiomar Perez de Nanclares; Elena Gastaldo; Lorna W Harries; Oscar Rubio-Cabezas; Luis Castaño (PLoS ONE, 2012)
The aim of this study was to characterize the genetic etiology in a patient who presented with permanent neonatal diabetes at 2 months of age.Regulatory elements and coding exons 2 and 3 of the INS gene were amplified and sequenced from genomic and complementary DNA samples. A novel heterozygous INS mutation within the terminal intron of the gene was identified in the proband and her affected father. This mutation introduces an ectopic splice site leading to the insertion of 29 nucleotides from the intronic sequence into the mature mRNA, which results in a longer and abnormal transcript.This study highlights the importance of routinely sequencing the exon-intron boundaries and the need to carry out additional studies to confirm the pathogenicity of any identified intronic genetic variants.